Identification of Science Laboratory Service Quality from the Perspective of Junior High School Students in Majene Regency Using the Importance Performance Analysis Method - A. Mutmainnah Taslim; Wahyuni Adam; Nasran Aziza (Journal of Science Education Research, 2026)
This study aims to obtain comprehensive and detailed information regarding the quality and priority of science laboratory services for improving the quality of science laboratory services at the junior high school level in Majene Regency. This research used a quantitative method with a descriptive approach. The population of this study was all junior high school students in Majene Regency. The sample size was 184 students, obtained through purposive sampling. The data collection technique used was a questionnaire. The instruments used consisted of a validation sheet and a questionnaire, both of which had undergone content validation by two experts. The instrument validation stage yielded an internal consistency coefficient (content validity) of 0.83 > 0.75, indicating that the questionnaire is valid and can be used in the research activities. The data were analyzed using Importance Performance Analysis. This involved two calculations: a conformity level calculation using Microsoft Excel and a priority dimension calculation using Simple Scatter in SPSS version 26. The results of the study indicate that the quality of science laboratory services at the junior high school level in Majene Regency, from the students' perspective, is generally of high quality, as 93% of the items fall into the category of alignment between the service experienced and the expected service. Furthermore, five items were prioritized for improvement in the quality of science laboratory services at the junior high school level in Majene Regency, spread across the dimensions of reliability, responsiveness, assurance, and empathy.